Effective e-learning? Multi-tasking, distractions and boundary management by graduate students in an online environment - Winter, J.; Cotton, D.; Gavin, J.; Yorke, Jon (Routledge, 2010)
This paper reports the findings of a small-scale study that documented the use of information technology for learning by a small group of postgraduate students. Our findings support current knowledge about characteristics displayed by effective e-learners, but also highlight a less researched but potentially important issue in developing e-learning expertise: the ability of students to manage the combination of learning and non-learning activities online. Although multi-tasking has been routinely observed amongst students and is often cited as a beneficial attribute of the e-learner, there is evidence that many students found switching between competing activities highly distracting. There is little empirical work that explores the ways in which students mitigate the impact of non-learning activities on learning, but the evidence from our study suggests that students employ a range of ‘boundary management’ techniques, including separating activities by application and by technology. The paper suggests that this may have implications for students’ and tutors’ appropriation of Web 2.0 technologies for educational purposes and that further research into online boundary management may enhance understanding of the e-learning experience.